Polyphenols from the Mediterranean herb rosemary (Rosmarinus officinalis) for prostate cancer - Sakina M Petiwala; Angela G Puthenveetil; Jeremy eJohnson; Jeremy eJohnson (Frontiers Media S.A., 2013)
The Mediterranean diet is rich in fruits and vegetables and has been associated with a variety of health benefits including cancer prevention. One aspect of the diet that has not received enough attention is Mediterranean herbs. Specifically, rosemary and its polyphenolic diterpenes (carnosic acid and carnosol) are known to possess antioxidant activity that may be beneficial for cancer control. Herein, we describe the in vitro and in vivo studies carried out towards understanding the molecular mechanisms of carnosic acid and carnosol leading to inhibition of prostate cancer. The reported findings suggest that these polyphenols target multiple signaling pathways involved in cell cycle modulation and apoptosis. Further work is required to understand its potential for health promotion and potential drug discovery for prostate cancer chemoprevention.